The Growth Pattern of Nyale Worm (Eunice, sp. Polychaeta) From Pahiwi Coastal, Sumba Island, Indonesia - Njurumana, Steven Nggiku; Widianingsih, Widianingsih; Hartati, Retno; Ginzel, Fanny Iriany (Universitas Diponegoro, 2025)
Nyale (Eunice sp) is a polychaeta worm that belongs to the Phylum Annelids. Nyale (Eunice sp) appeared only once on Pahiwi Beach, West Sumba. Its appearance is often associated with the traditions of te west Sumbanese people. Nyale’s growth pattern is not yet known, so this research aims to determine Nyale’s growth pattern. Nyale samples were taken in the morning before sunrise by hand picking at the location of Pahiwi Coastal Waters, West Sumba. Based on the analysis results, the growth pattern of the Nyale is negative allometric, with a value of b=1.05. the correlation value obtained from the relationship between length and weight is 0.68. this also shows that an increase in length and weight.